ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN MEMILIH PRODUK SYNGENTA ATAU NON SYNGENTA (KASUS PADA PETANI SAYUR DI KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG) - Arianti, Nyayu Neti; Priyono, Basuki Sigit; Women, Elsi (Jurnal AGRISEP, 2007)
This research aims are to know the reason of consumers chosen and the factors influencing decision of consumers chosen Syngenta or Non Syngenta product.This reseach was apllied at Selupu Rejang Sub district Rejang Lebong District. Analysis methods which used are descriptive analysis and quantitative analysis. Descriptive analysis that is giving common picture to reseach object, reasons pushing consumers to chosen and consume the Syngenta or Non Syngenta product, and also explain the proportion usage of  insecticide, fungicide and haerbicide from Syngenta or Non Syngenta product. Quantitative analysis is to know the factors of influencing consumers decision in chosen Syngenta or Non Syngenta product by using regression model of  logit. Result of analysis indicate that the reasons of consumers chosen Syngenta product are efective to use, good harvest, price reached, more use by the farmers. And than, the reasons of consumers chosen Non Syngenta product are efective to use, swafety to use, good harvest and more use by the farmers Key words :  influencing decision,consumer, chosen